Smoke on the water—Oral fluid analysis at sea. (September 2017) - Griffiths, Andrew; Leonars, Richard; Hadley, Lenore; Stephenson, Mark; Teale, Richard
Highlights: The oral fluid of 953 skippers in charge of water vessels were analysed for three illicit drugs in Queensland, Australia. 13% of skippers tested positive to at least one illicit drug. THC was the most common drug identified (91% of positive specimens). Skippers of both commercial and leisure vessels were tested. Planning is the key to conducting successful waterside oral fluid testing. Abstract: This study outlines the operational challenges and findings of an illicit drug oral fluid testing program carried out on the skippers (those in charge) of water vessels in Queensland, Australia. Between 2010 and 2016, 953 tests of skippers were conducted on water (waterside) for three proscribed illicit drugs; delta-9-tetrahydrocannabinol (THC), methylamphetamine (MA) and 3, 4-methylendioxymethylamphetamine (MDMA). 126 (13%) of the skippers tested returned an on-site positive during waterside testing, 125 were confirmed positive for one or more illicit drug by subsequent laboratory analysis, whilst one skipper did not provide an oral fluid sample for confirmatory analysis. The skippers were entirely male (100%) with an average age of 39 years (range 17–59). THC was by far the most common drug detected (91%); MA was detected in 22% of skippers and a combination or THC and MA in 14% of specimens. MDMA was identified only once during the study, this being in combination with THC. As a single waterside operation can take more than a week, operational pre-planning becomes essential. Aspects of the operation such as, weather, shift times, food, testing consumables, sleeping quarters, hygiene, liaison between different agencies and multiple other factors need to be taken into account prior to commencement. A waterside operation must be mobile and, in Queensland at least, able to cover a large area of water. There is also a much lower volume of vessels likely to be encountered at sea compared to a roadside operation targeting motor vehicles.